2020
DOI: 10.25259/ijms_55_2020
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of hepatic encephalopathy admitted in a tertiary care center

Abstract: Objectives: Few of the common symptoms for which cirrhotic patient seeks medical care are gastrointestinal bleed, abdominal distension (ascites), altered sensorium (hepatic encephalopathy [HE]), etc. This study was done to look at the spectrum of HE among cirrhotic patients admitted in a tertiary care center. Material and Methods: This hospital-based study was carried on 36 HE patients (with liver cirrhosis and age >18 years) admitted in the department of gastroenterology of a tertiary care center, betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…In a study of 91 patients, Pal et al, found 51% of patients belonged to Child-Pugh Class B followed by Class C in 35% and only 14% in class A. 9 Soni et al, reported that majority patients (77.8%) belonged to CTP Class C. 10 In our study, 33 patients (66%) had lower skeletal mass index. Kumar et al, reported sarcopenia in 47.8% of patients.…”
Section: Discussionsupporting
confidence: 49%
“…In a study of 91 patients, Pal et al, found 51% of patients belonged to Child-Pugh Class B followed by Class C in 35% and only 14% in class A. 9 Soni et al, reported that majority patients (77.8%) belonged to CTP Class C. 10 In our study, 33 patients (66%) had lower skeletal mass index. Kumar et al, reported sarcopenia in 47.8% of patients.…”
Section: Discussionsupporting
confidence: 49%